2008
DOI: 10.1590/s2236-89062008000400012
|View full text |Cite
|
Sign up to set email alerts
|

Polypores from a Brazilian pine forest in Southern Brazil: pileate species

Abstract: A fungal survey in the National Forest of São Francisco de Paula, in southern Brazil, displayed 38 pileate polypores species (eight Hymenochaetales and 30 Polyporales). Amauroderma coltricioides T.W. Henkel, Aime & Ryvarden and Inonotus fulvomelleus Murrill are recorded for the fist time from Brazil, whereas Antrodiella multipileata Log.-Leite & J.E. Wright and Junghuhnia minuta I. Lindblad & Ryvarden are new records to Rio Grande do Sul State. Keys to species and remarks on the taxa are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…duportii and Microporellus brasiliensis are new records for Rio Grande do Sul State. Identification keys adapted from Silveira et al (2008) are presented including all the species found in the region, as well as comments on the twenty species previously unregistered. Microscopic drawings of the newly recorded species and a image of M. brasiliensis are also presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…duportii and Microporellus brasiliensis are new records for Rio Grande do Sul State. Identification keys adapted from Silveira et al (2008) are presented including all the species found in the region, as well as comments on the twenty species previously unregistered. Microscopic drawings of the newly recorded species and a image of M. brasiliensis are also presented.…”
Section: Resultsmentioning
confidence: 99%
“…After that, several other taxonomic researchers have been undertaken in the State on that group (Silveira & Guerrero 1991, Groposo & Loguercio-Leite 2002, Coelho et al 2006, Coelho et al 2009, Westphalen et al 2010, Reck et al 2011, Westphalen et al 2012. Silveira et al (2008) did a survey of the pileate polypores from the São Francisco de Paula National Forest, providing a preliminary identification key for 38 species found in that study. More recently, another polypores survey was conducted in the municipality of São Francisco de Paula, RS, including collections of specimens in the National Forest, as well as the nearby areas.…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopic and microscopic data of the specimens were obtained following traditional methodologies (SINGER, 1975;RYVARDEN, 1991) and the colors were determined according to Munsell (1975). All specimens are deposited in the herbarium FLOR at the Universidade Federal de Santa Catarina.…”
Section: Methodsmentioning
confidence: 99%
“…However, A. camerarium differs in the pilear cover, which is formed by a cortex, and A. sprucei can be distinguished by the size (11-13 × 9-11mm in A. omphalodes and 9-10 × 7-8mm in A. sprucei) of the basidiospores (FURTADO, 1981 Silveira et al (2008) and A. calcigenum (Berk.) Torrend recorded by Gomes-Silva et al (2010).…”
Section: Description In Furtado (1981)mentioning
confidence: 99%
“…However, even with the main mycological effort focused in the Atlantic Forest biome, it seems that we are still far from knowing the whole polypore diversity. A further 24 species have been added to the Atlantic Forest list by Drechsler-Santos et al (2008), Silveira et al (2008Silveira et al ( ["2009), Baltazar et al (2009bBaltazar et al ( , 2010a, Campacci & Gugliotta (2009), Coelho et al (2009), Gomes-Silva et al (2010a), Gugliotta et al (2010), Meijer (2010), Westphalen et al (2010a,b), Gibertoni et al (2011) and Reck et al (2011). Seven of these species were described as new taxa, while 11 were reported for the first time in Brazil.…”
Section: Introductionmentioning
confidence: 99%